THE EFFECT OF ELECTRO MAGNETIC FIELD INTENSITY TO BIODIESEL CHARACTERISTICS (Jurnal Pendidikan Fisika Indonesia, 2017)
Various studies of diesel fuel optimization have been done, one of them by using a permanent magnet on the fuel line, the lack of magnetic field intensity decreases along with time increasing by using an electromagnetic field. The purpose of this study is to analyse the biodiesel fuel characteristics due to exposure of electromagnetic fields in terms of the viscosity and vibration of these fuel molecules. Electromagnetic field is generated from wire coil of 5000-9000 on galvanum pipe with diameter of 1.5 cm and length of 10 cm and connected to 12 V batteries. Here, biodiesel fuel is inserted in a galvanum tube, magnetized for 1200 s, and tested its viscosity of the falling ball system by viscometer. Fuel functional groups as well as vibrations between fuel molecules are tested with FTIR. The results show that the magnetized fuel changes. The viscosity of fuels from 2933 to 2478 and an increasing in the absorption of fuel molecules ranges from 13-58%. Therefore, the increasing of vibrating fuel molecules decreases its molecular attraction tug. These indicate that the magnetized fuel molecule causes a changing in the fuel molecule, cluster becomes de-clustered. It is a potential method to clarify the phenomenon of fuel magnetization due to its efficient combustion process.